Open Legal Policy in Constitutional Court Decisions: Constitutional Limits and Its Issues in the Indonesian State Administration System - Lusia Indrastuti; F.X. Hastowo Broto Laksito (Lembaga Pengembangan Kinerja Dosen, 2026)
The doctrine of open legal policy is a jurisprudential construction of the Constitutional Court that provides space for lawmakers to formulate norms as long as they do not contradict the 1945 Constitution of the Republic of Indonesia. Nevertheless, the application of this doctrine in the practice of law testing has raised various constitutional problems, particularly concerning the limits of authority between legislators and the Constitutional Court, as well as the protection of citizens' constitutional rights. This research aims to analyze the concept and construction of open legal policy within the Indonesian constitutional system and to formulate the constitutional limits of its application in Constitutional Court decisions. This research is a normative legal study with an approach based on legislation, a conceptual approach, and a case approach. The legal materials used include the 1945 Constitution, relevant legislation, and pertinent Constitutional Court decisions. The research results indicate that open legal policy cannot be interpreted as absolute freedom for lawmakers, but must be limited by the principle of constitutional supremacy, protection of constitutional rights, and the principle of proportionality as reflected in Article 28J paragraph (2) of the 1945 Constitution. The ambiguity of the parameters for applying this doctrine has the potential to cause inconsistencies in rulings and disrupt legal certainty. Therefore, a more precise and consistent formulation of constitutional limits is necessary to maintain the balance between representative democracy and constitutional oversight.